2017
DOI: 10.1038/nature23018
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale physical activity data reveal worldwide activity inequality

Abstract: Understanding the basic principles that govern physical activity is needed to curb the global pandemic of physical inactivity1–7 and the 5.3 million deaths per year associated with in-activity2. Our knowledge, however, remains limited owing to the lack of large-scale measurements of physical activity patterns across free-living populations worldwide1, 6. Here, we leverage the wide usage of smartphones with built-in accelerometry to measure physical activity at planetary scale. We study a dataset consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
556
6
29

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 765 publications
(659 citation statements)
references
References 39 publications
29
556
6
29
Order By: Relevance
“…Although we suspect the data has serious bias, Physical Activity and Health-Related Quality of Life such as smartphone carrying time (depending on the types of clothing differed by country), the objective PA data give important insights into the understanding of physical inactivity prevalence. 35 Generally, there is a clear worldwide variation in physical inactivity prevalence, where physical inactivity is more common in countries of high income than in those of low income. However, globally and regardless of income level of a country, the low-income people had more physical inactivity than those with high income.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we suspect the data has serious bias, Physical Activity and Health-Related Quality of Life such as smartphone carrying time (depending on the types of clothing differed by country), the objective PA data give important insights into the understanding of physical inactivity prevalence. 35 Generally, there is a clear worldwide variation in physical inactivity prevalence, where physical inactivity is more common in countries of high income than in those of low income. However, globally and regardless of income level of a country, the low-income people had more physical inactivity than those with high income.…”
Section: Discussionmentioning
confidence: 99%
“…6 These changes have led to rapid urbanization and poorer lifestyle choices, such as unhealthy dietary habits and inadequate PA. 7 Nationwide surveys have highlighted an increasing trend of disease burden and prevalence among the Malaysian population. 8 The Fourth National Health and Morbidity Survey of Malaysia reported that the prevalence of non-communicable disease (NCD) risk factors of obesity, hypercholesterolemia, and hypertension were 27.2%, 35.1%, and 32.7%, respectively, in Malaysia. 9 The respondents from the urban areas reported higher prevalence of chronic illness compared to those from rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Health promotion plays the role of transmuting the fragmentation of care spaces and claiming the social functions of the city, strengthening the logic of universality and integrality 4 . Among the global fronts of health promotion, physical activity is a priority theme 5,6 considering the epidemiological importance and the social gradients of this behavior in the population 7,8 . Increasing access to public areas for physical activities or sports has been an urban policy to encourage such practice 2 .…”
Section: Introductionmentioning
confidence: 99%
“…4 or less) during the baseline period, a generic 5,000 daily step goal was provided. Five thousand daily steps is approximately the number of steps taken by the average Canadian adult as measured by a popular smartphone-based activity tracking app [38].…”
Section: Baseline Periodmentioning
confidence: 99%